Analysis of birth rate, neonatal morbidity, and mortality during the COVID-19 pandemic and martial law in Ukraine - O.P. Volosovets; S.V. Tsemashko; I.O. Loginova; S.P. Kryvopustov; T.I. Shevtsova; O.V. Ilyin; O.F. Chernii; L.M. Helescul; O.V. Holik (Zaslavsky O.Yu., 2023)
Background. Ukraine is currently experiencing a rapid decline in fertility due to the COVID-19 pandemic and martial law. The purpose was to study birth rate fluctuations and changes in the structure of early neonatal morbidity and mortality at Kyiv City Maternity Hospital 6 during the COVID-19 pandemic and martial law and to compare the obtained findings with national statistical data. Materials and methods. A retrospective analysis and assessment of birth rate fluctuations, early neonatal morbidity, and mortality were carried out for 2020-2022 using both the health care industry statistics and the data obtained from Kyiv City Maternity Hospital 6. Results. Increased morbidity and high psycho-emotional stress levels among pregnant women contributed to a more frequent occurrence of neonatal disorders associated primarily with intrauterine hypoxia and perinatal infection. The improvements in newborn care and concurrent reduction in the preterm birth rate at the maternity hospital providing level II perinatal care services have been associated with a decreased rate of early neonatal mortality over the past three years. Conclusions. The use of modern fetal monitoring technologies, the timely diagnosis and treatment of perinatal pathology, and improvements in the organization of newborn care help preserve child health and prevent mortality.